Kontribusi Keterampilan Guru Dalam Pembelajaran dan Motivasi Berprestasi Terhadap Tanggung Jawab Siswa dan Dampaknya pada Kemandirian Belajar PKn SMP - Rahayu, Hesti Oki; Sumardjoko, Bambang; Sumardi, Sumardi (Universitas Muhammadiyah Surakarta, 2014)
The purposes of this research are to find out the available contribution and to measure the teachers? learning capacity and need of achievement to students? responsibility, students? responsibility to the self-directed learning and the teachers? learning capacity, need of achievement and students? responsibility to the self-directed learning in Civic Education on the Roudlotus Saiddiyah Gunung Pati Semarang Integrated Islamic Junior High School. This is a quantitative research. The location of this research on the Roudlotus Saiddiyah Gunung Pati Semarang Integrated Islamic Junior High School. This research is begun in the end of the second semester academic year of 2012/2013. The samples are 114 for the population as many as 172 with 5% error. Technique of sampling is used proportional sampling. Technique of collecting data is used questioner. The results of this research are 1) there is a weak and significant contribution from the teachers? learning capacity and need of achievement to the students? responsibility in learning Civic Education on the Roudlotus Saiddiyah Gunung Pati Semarang Integrated Islamic Junior High School, 2) there is a weak and significant contribution from the students? responsibility to the students? self-directed learning in learning Civic Education on the Roudlotus Saiddiyah Gunung Pati Semarang Integrated Islamic Junior High School, 3) there is a weak and significant contribution from the teachers? learning capacity, the need of achievement and the students? responsibility to the students? self-directed learning in learning Civic Education on the Roudlotus Saiddiyah Gunung Pati Semarang Integrated Islamic Junior High School.